Penerapan Latihan Sensorimotor Untuk Meningkatkan Kemampuan Menulis Pada Anak Autistic Spectrum Disorder - Musjafak Assjari; Eva Siti Sopariah (Jurnal Pendidikan dan Kebudayaan, 2011)
The goal of this research is to prove that the application of sensorimotor training can improve writing skills and the writing in Autistic Spectrum Disorder (ASD) children, the research question posed is: Does the application of sensory motor training improve writing skills in Autistic Spectrum Disorder (ASD) children? The method of research applied quantitative approaches, and for the intervention and data analysis, the study used the method of Single Subject Research (SSR) model of Multiple Baseline Design of Variable Cross (plural design between variables) and the design of A - B - A. with a unit of measurement duration and percentage. The results are consistent with the research questions and basic assumptions that the study subjects experienced significant improvement in writing skills. Therefore sensory motor training can be used as a reference in improving or optimizing the ability of vestibular, tactile, kinesthetic and propioseptif which is prasarat writing skills possessed by children Autistic Spectrum Disorder (ASD). ABSTRAKTujuan penelitian ini dimaksudkan untuk membuktikan bahwa penerapan latihan sensorimotor dapat  meningkatkan  kemampuan  menulis  dan  hasil  menulis  pada  anak Autistic  Spectrum  Disorder (ASD).Metode penelitian menggunakan pendekatan kuantitatif, serta dalam intervensi dan analisis data menggunakan metode Single Subject Research (SSR)model Design Multiple Baseline Cross Variable(disain jamak antar variabel) dan disain A – B – A. dengan satuan ukur durasi dan persentase. Hasil penelitian ini  menunjukkan  bahwa  secara  nyata  subyek  penelitian  mengalami  peningkatan  dalam  kemampuan menulis. Oleh karena itu, latihan sensorimotor ini dapat dijadikan sebagai acuan dalam meningkatkan atau mengoptimalkan kemampuan vestibular, taktil, kinestetik dan propioseptif yang merupakan keterampilan prasarat menulis yang dimiliki oleh anak Autistic Spectrum Disorder (ASD).